Let a n = 4 − 3 n , for all integers n ≥ 1 . Define
f ( x , y ) = x + i = 1 ∑ ∞ [ ( 3 i ⋅ i ! ∏ j = 1 i a j ) x a i + 1 y i ]
for all real numbers x and y . Determine the positive integer k such that f ( 1 9 , k ) = 2 0 .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
There is a slight error in your expansion of ( x 3 + y ) 1 / 3 . It should be x + n = 2 ∑ ∞ [ ( 3 n ⋅ n ! ∏ i = 1 n − 1 a i ) x a n y n − 1 ] . However, there is a more serious error. The generalized binomial theorem can be applied to ( 1 + z ) r only if ∣ z ∣ ≤ 1 . Thus, if you write ( x 3 + y ) 1 / 3 = x ( 1 + x 3 y ) 1 / 3 , then the generalized binomial theorem applies only if ∣ y ∣ ≤ ∣ x 3 ∣ . In particular, if x = 1 5 , then y must satisfy ∣ y ∣ ≤ 1 5 3 = 3 3 7 5 .
If you set y = 4 6 2 5 , then you'll find that ( 3 n ⋅ n ! ∏ i = 1 n − 1 a i ) x a n y n − 1 diverges as n goes to infinity, so the sum is not well-defined.
Log in to reply
Thanks for pointing that out! This would otherwise have made a nice problem about Taylor series.
Done the same way.
The problem has now been updated and the correct answer is now 1191.
Those who previously answered 4625 were marked wrong, because f ( 1 5 , 4 6 2 5 ) = 2 0 .
Can you update your solution, and remember to mention the radius of convergence? Thanks!
Problem Loading...
Note Loading...
Set Loading...
Consider the function F ( x , y ) = 3 x 3 + y . If we write the function in the form ( x 3 + y ) 1 / 3 , we can use the generalized version of the binomial theorem to expand this. We get
( x 3 + y ) 1 / 3 = ( 0 1 / 3 ) x + ( 1 1 / 3 ) x − 2 y + ( 2 1 / 3 ) x − 5 y 2 ⋯ .
Also,
( n 1 / 3 ) = n ! ( 1 / 3 ) ( 1 / 3 − 1 ) ( 1 / 3 − 2 ) ⋯ ( 1 / 3 − n + 1 ) = n ! ( 1 / 3 ) ( − 2 / 3 ) ( − 5 / 3 ) ⋯ ( a n / 3 ) = 3 n ⋅ n ! ∏ i = 1 n a i . .
Finally, notice that the exponent on x for the n th term in our expanded expression, excluding the first x , actually equals a n + 1 , and the corresponding exponent on y is n . Combining all this, we get
( 0 1 / 3 ) x + ( 1 1 / 3 ) x − 2 y + ( 2 1 / 3 ) x − 5 y 2 ⋯ = x + n = 1 ∑ ∞ [ ( 3 n ⋅ n ! ∏ i = 1 n a n ) x a n + 1 y n ] = f ( x , y ) .
Thus, F ( x , y ) = f ( x , y ) = 3 x 3 + y . To solve the problem, we need to find the integer k such that 1 9 3 + k = 2 0 3 . This value is k = 2 0 3 − 1 9 3 = 2 0 2 + 2 0 ( 1 9 ) + 1 9 2 = 1 1 4 1 .
We still need to show that this value of k will indeed make the series equal 2 0 i.e. if the series converges or diverges. The binomial expansion of ( x + y ) n , for a real number n that is not a nonnegative integer, will converge if ∣ x ∣ > ∣ y ∣ and diverge otherwise. In this case, since ∣ ∣ 1 9 3 ∣ ∣ = 6 8 5 9 is clearly greater than 1 1 4 1 , our series will converge, so f ( 1 9 , 1 1 4 1 ) = 2 0 .